3D‐Printed End‐of‐Arm for Smarter Packaging: Anubis' innovative industrial 3D‐printed end‐of‐arm tooling solution enables Langen Group to lighten load on their customer's robotic packaging line. Issue 2 (12th April 2017) - Unknown
Abstract: New robots for the pick‐n‐pack line were already on order. A major American food producer's equipment supplier, the Langen Group, began designing the end‐of‐arm tool that would enable the robots to pick up wrapped, stacked crackers and place them into cardboard boxes. Then the engineers ran into a challenge.